Production and Potential Applications of Bioconversion of Chitin and Protein-Containing Fishery Byproducts into Prodigiosin: A Review - Wang, San-Lang (Molecules, 2020)
The technology of microbial conversion provides a potential way to exploit compounds of biotechnological potential. The red pigment prodigiosin (PG) and other PG-like pigments from bacteria, majorly from Serratia marcescens, have been reported as bioactive secondary metabolites that can be used in the broad fields of agriculture, fine chemicals, and pharmacy. Increasing PG productivity by investigating the culture conditions especially the inexpensive carbon and nitrogen (C/N) sources has become an important factor for large-scale production. Investigations into the bioactivities and applications of PG and its related compounds have also been given increased attention. To save production cost, chitin and protein-containing fishery byproducts have recently been investigated as the sole C/N source for the production of PG and chitinolytic/proteolytic enzymes. This strategy provides an environmentally-friendly selection using inexpensive C/N sources to produce a high yield of PG together with chitinolytic and proteolytic enzymes by S. marcescens. The review article will provide effective references for production, bioactivity, and application of S. marcescens PG in various fields such as biocontrol agents and potential pharmaceutical drugs.